ANALISIS PIUTANG USAHA DALAM PENYUSUNAN ANGGARAN PIUTANG PT XYZ - Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2017)
ABSTRACTSales is the core of the company's activities, but sales are not generating cash, generating sales of receivables, and further if the receivables are collectible will be converted into cash. Sales management and billing that will either make healthy company, but if the management of billing generate sizeable loss reserve accounts, the operation of the company would be disrupted. Analysis of sales resulting receivables budget can provide views of future cash receipts will come, so the good management of the budget accounts will provide realization of receivables that exceed the budget itself.XYZ is a manufacturing company, receivables management companies generate receivables loss reserves amounted to 0.78%, with a pattern of acceptable receivables 0.46% sales month, 52% received the next month, 38% received in the next two months, and 9.54% received last month. Keywords: Sales, Account Receivable, budget Accounts